Dualisme Pengaturan Perkawinan Beda Agama - Assyifa Rachmat, Lavita; Ahmad Yani, Encep (UNES Law Review, 2024)
This research was motivated by the marriage of couples with different beliefs, called interfaith marriages. This type of marriage was originally permitted based on Law Number 24 of 2013, amendment to Law Number 23 of 2006 concerning Population Administration, then it was not permitted (prohibited) based on the Supreme Court Circular. (SEMA) Number 2 of 2023. The aim of this research is to determine the dualism of interfaith marriage arrangements. This research uses descriptive analytical methods with a normative juridical approach. The research results show that this inconsistency occurs because it is explicitly stated in Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage and Article 44 of the Instruction of the President of the Republic of Indonesia Number 1 of 1991 concerning the Compilation of Islamic Law which states that marriage between different religions is prohibited. The Surabaya District Court has decided case No.916/Pdt.P/2022/PN.Sby and has been confirmed by Supreme Court Decision Number 1400K/PDT/1986, the essence of the decision is to allow interfaith marriage between Rizal Adikara who adheres to Islam and Eka Debora Sidauruk who adheres to Christianity. The results of the research concluded that after the Supreme Court Circular Letter (SEMA) Number 2 of 2023, all interfaith marriages were prohibited.